Analisis Dampak Cuaca Ekstrem di Samudra Hindia terhadap Kerusakan Mainmast pada Kapal MV Isa Golden - Hoyrol Fatah; Mudiyanto Mudiyanto; Dedy Kristiawan (Port Management and Maritime Administration Journal, 2026)
This study, entitled "Analysis of the Impact of Extreme Weather in the Indian Ocean on Mainmast Damage Aboard MV ISA GOLDEN," examines the effects of extreme weather conditions on the Mainmast, which serves as a vital structural component supporting the vessel's navigation and communication systems. The study aims to analyze the impact of extreme weather on Mainmast damage and identify the most dominant factor contributing to its structural failure. A qualitative research method with a descriptive case study approach was employed. Data were collected through field observations, semi-structured interviews with the Captain, Chief Officer, Second Officer, and Boatswain, as well as document analysis, including operational records, incident reports, damage reports, the Planned Maintenance System (PMS), and technical documentation. The findings reveal that extreme weather conditions, characterized by strong winds, high waves, heavy rainfall, and continuous rolling and pitching motions, generated repetitive dynamic loads acting on the Mainmast. The most dominant factor contributing to the damage was the deterioration of structural strength caused by corrosion and material fatigue, which was further exacerbated by dynamic loading during the voyage, ultimately resulting in the structural failure of the Mainmast. This study provides empirical evidence of the relationship between extreme weather, dynamic loading, and ship structural reliability, while serving as a reference for improving inspection systems, preventive maintenance, and risk mitigation strategies to enhance maritime safety.